Climate change and the forest sector : - Rosenbaum, Kenneth L. (FAO, 2004)
The likely economic and ecological impacts of climate change poses a daunting international challenge, which will require pioneering efforts in science, politics, pollution control, forests management and law in response. This publication examines the development of international law on climate change and discusses key legal and institutional issues that will need to be considered by national and subnational legislative bodies in relation to forest management based mitigation activities.